UPAYA PENINGKATAN KUALITAS PELAKSANAAN PENDIDIKAN AGAMA KATOLIK BAGI SISWA NEGERI DI GEREJA KATOLIK PADA WILAYAH PROVINSI DKI JAKARTA - Salman Habeahan (Lembaga Penelitian STKIP Widya Yuwana, 2022)
This article aims to examine the implementation of Catholic religious education in the Church (Parish) for Catholic students who attend public schools, and do not receive Catholic religious education because there are no Catholic teachers who teach in public schools at the elementary, junior high, high school and vocational school levels. The research was conducted on 47 Catholic churches that carry out Catholic religious education for Catholic students studying in public schools in the Special Capital Region of Jakarta with 78 respondents. The finding is that quite some public schools at the elementary, junior high, high school, and vocational levels with 15 students and above do not receive Catholic teaching in their schools because there are no Catholic religious teachers who teach at these schools. The main problem of this research is: can efforts to improve the quality of Catholic religious education for public students in the Catholic Church in the Special Capital Region of Jakarta overcome the problem of the lack of Catholic religious teachers teaching in public schools?. Efforts to improve the quality of the implementation of Catholic religious education for public students carried out in the Catholic Church have a positive impact on fostering Catholic students and in fulfilling the obligations of academic demands to get the value of Catholic religious education and character in public schools. This research recommends the importance of improving the quality of Catholic religious education for public students in the Church; such as coaching for Catholic Religion teachers who teach in the church and the assessment process so that it is by the assessment standards in the applicable curriculum. For this reason, it is important to collaborate with the Directorate General of Catholic Guidance at the Ministry of Religion of the Republic of Indonesia to prepare a budget for the development of Catholic religious teachers/catechists who teach Catholic students attending public schools. And the importance of good planning by the Directorate General of Catholic Guidance at the Ministry of Religion of the Republic of Indonesia and the Provincial Government of DKI Jakarta for the formation of Catholic Religion teachers in public schools. In addition, optimal efforts and cooperation are needed for the Catholic Community Service Regional Office of the Ministry of Religion of the Special Capital Region of Jakarta with the Jakarta Archdiocese Catechetical Commission, the role of family/Parents, so that the implementation of Catholic teaching for public students at 47 churches/parishes in DKI Jakarta can be implemented. The quality is improved because it can overcome the problem of the shortage of teachers who teach Catholicism in public schools.